A Systematic Literature Review on LLM-Based Content Classification - Cosme, D.; Galvão, A.; Brito e Abreu, F. (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2026)
This review examines how LLMs, particularly those using transformer architectures, have addressed persistent challenges in text classification through their advanced context understanding and generative capabilities. Despite significant progress, the review highlights gaps in current research, such as the need for greater transparency, reduced computational cost, and better management of model hallucinations. The paper concludes with recommendations for future research to improve the use of LLMs in content classification and ensure their effective use in various domains.